Telescopic otology referrals: Evaluation of feasibility and acceptability. Issue 2 (3rd March 2020) - Cottrell, Elizabeth; George, Ajith; Coulson, Chris; Chambers, Ruth
Abstract: Objective: A remote telemedical otology referral and advice service was introduced to interested general practices. General practitioners (GPs) were given a new device, "endoscope‐i" that combines an optimized smartphone high definition video app with an otoendoscope. They were specifically trained to examine and capture images of patients' eardrums, which were sent electronically with a summary of clinical information and an in‐app hearing testing (if required), for specialist advice to two ear, nose, and throat (ENT) consultants. We describe the findings from an evaluation of the first 6 months of this service to establish the feasibility and acceptability of an otology telemedical referral and advice service. Methods: The new service was advertised to GP practices in Northern Staffordshire. All interested GPs were provided with training and equipment to deliver the remote referral service. Data were collected from GPs at baseline, informal feedback in response to referral outcomes and end of service feedback. Referral data were collected routinely during the service delivery. Results: Fifteen GP leads from 15 practices received training and equipment. One quickly lost the equipment. Of the remaining 14 practices, eight sent a total of 53 remote referrals using this technology over 6 months. The most common reason for referral was an uncertainty of what could be seen in or around the eardrum. The primary barrier for implementation was lack of wireless internet connections within practices. GPs reported that they used this technology to share examination findings with patients. Conclusions: GPs were positive about the technology, from initial engagement with training and after advice were given. Some GPs expanded the role of the technology to a consultation aid. Referral volume was manageable. Commissioners should consider tariffs structures for such services; empirical cost‐effectiveness and workload‐impact evaluation would inform this.